Surface Treatments for RC Structures in Marine Environments: A Literature Review - Hoosain, Ashfaaq (Department of Civil Engineering, 2024)
If designed correctly, structures made from reinforced concrete have the potential to be very durable and are capable of enduring a wide variety of hostile environmental conditions. However, structural design and engineering standards that are currently available do not provide for sufficient and continuous durability compliance. As such, during the design phase, the long-term durability of concrete structures is often overlooked. Inadequate durability may result in premature deterioration and significant unforeseen repair costs. Many reinforced concrete structures worldwide are reaching their designed service life, and it is unlikely that they will be decommissioned and rebuilt, primarily due to financial difficulties. As a result, there is an amplified need to maintain and extend the service life of existing structures and ensure that all newly built structures last as long as possible. The harsh marine environment that causes the steel reinforcement to corrode in a concrete structure is one of the primary causes of premature deterioration. Whilst patch repairing defective concrete is often the first step in correcting premature deterioration, it may not prove to be long- lasting, without the added use of surface treatment systems, especially in non-patch-repaired locations. Reinforcement corrosion in marine environments affects the durability of structures due to the high presence of chlorides and moisture availability. The chloride ions in seawater reduce the protective oxide coatings that form on the reinforcement, thereby inducing corrosion. With that being said, there is an increased demand for the application of surface treatment systems, as they provide reinforced concrete structures in marine environments with protection from deterioration related to the ingress of chloride and moisture. This research critically examines the protective benefits of surface protection systems applied to reinforced concrete structures in marine environments. It focuses on the deterioration of reinforced concrete structures in marine environments and conducts a comprehensive and in- depth literature review of surface treatment systems. A particular focus is on the service life extension and the durability enhancement that these treatments have on concrete structures. According to BS EN 1504, surface treatments can be classified into four types of surface protection systems: surface coatings, hydrophobic impregnations, impregnations or surface sealers, and screeds and overlays. Their function, types and uses, and performance in marine environments, are reviewed. While the study demonstrated that all surface treatments protected reinforced concrete structures, the analysis of the literature showed that surface coatings, particularly polyurethane coatings, provided the best protection for reinforced concrete structures in marine environments. Studies have shown that these coatings can increase the service life of these structures by up to 7.8 times compared to untreated concrete.A summary of the different surface treatment systems is discussed in detail in this dissertation. The summary includes the different types within a particular treatment system, the reason one would consider applying these systems, and a description of the benefits thereof. It may aid engineers and practitioners in selecting the correct treatment system for projects in marine environments. Furthermore, this research appraises various international standards and the status of specifications concerning the advances in the field. As existing infrastructure is increasingly ageing, the need for repair and protection is rapidly growing. In addition, the substantial development of new materials and methods for repairing and protecting reinforced concrete structures has led to the need for revised standards.